Allogenic MSC infusion in kidney transplantation recipients promotes within 4 hours distinct B cell and T cell phenotypes - Hendriks, Sanne H.; Heidt, Sebastiaan; Reinders, Marlies E.J.; Koning, Frits; van Kooten, Cees (Frontiers in Immunology, 2024)
Background: Infusion of mesenchymal stromal cells (MSCs) has been proposed as immunemodulatory therapy in solid organ transplantation. The use of allogenic MSCs could improve standardization and allow for direct availability of the product.The nonrandomized phase Ib Neptune clinical trial provided safety and feasibility data on the use of allogenic bone-marrow-derived MSCs, infused in 10 patients at week 25 and 26 post kidney transplantation. Here, we performed detailed analysis on the peripheral blood immune cell composition of these patients up to 52 weeks post transplantation. We used a 40 marker antibody panel with mass cytometry to assess potential effects of MSC therapy on the immune system.We showed minor changes in major immune lineages at week 27, 34 and 52 post kidney transplantation after MSC infusion at week 25 and week 26, confirming previous data with regular flow cytometry. However, in a direct comparison between pre-and post MSC infusion, as soon as 4 hours after MSC infusion, we observed a significant increase in cell numbers of B cell and T cell subsets that shared a unique expression of CD11b, CD11c, CD38, CD39, and Ki-67.Exploring these CD11b + CD11c + CD38 + CD39 + Ki-67 + B cells and T cells in the context of MSC infusion after kidney transplantation may be a promising avenue to better understand the immunological effects of MSC therapy.